2005
DOI: 10.1161/01.atv.0000187465.55507.85
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Renin-Angiotensin System Prevents Free Fatty Acid–Induced Acute Endothelial Dysfunction in Humans

Abstract: Objective-An elevated free fatty acid (FFA) level impairs endothelium-dependent vasodilation in humans, which may be pathophysiologically relevant to the development of endothelial dysfunction in patients with insulin resistance. We investigated the effect of inhibition of the renin-angiotensin system (RAS) on FFA-induced endothelial dysfunction. Methods and Results-Changes in forearm blood flow during intra-arterial infusion of acetylcholine were measured by plethysmography before and after systemic infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 27 publications
(31 reference statements)
2
47
0
3
Order By: Relevance
“…9 Our results strongly suggest that activated RAS predominantly contributes to FFA-induced endothelial dysfunction; however, the specific RAS systems that are involved must be identified. The experiments in the present study have partly identified these RAS systems.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…9 Our results strongly suggest that activated RAS predominantly contributes to FFA-induced endothelial dysfunction; however, the specific RAS systems that are involved must be identified. The experiments in the present study have partly identified these RAS systems.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, one simple and plausible explanation for FFAinduced, RAS-mediated endothelial dysfunction is the enhancement of NADPH oxidase activity and reactive oxygen species production in endothelial cells by Ang II from leukocytes. In fact, we demonstrated previously that vitamin C prevented FFA-induced endothelial dysfunction in humans 9 and that palmitate enhanced reactive oxygen species production and NADPH oxidase expression. 13 However, the enhanced release of Ang II from leukocytes, if any, was not detectable as changes in the plasma concentration of Ang II, the systemic blood pressure, or the forearm vascular tone in the present study, which raises doubts that the increased Ang II production in leukocytes could be functionally relevant to vascular function.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…They enhance skeletal muscle blood flow, improving insulin delivery and enhancing glucose uptake and metabolism in insulin-sensitive tissues [25,142,143].They also improve insulin-mediated glucose uptake by reducing the degradation of bradykinin and increasing the production of NO through their blockade of kininase II and ACE [133,144]. They enhance vascular sensitivity to insulin and improve endothelial function [145,146]. ACE inhibitors may prevent or reduce Ang II-mediated interference with insulin-signaling pathways, evidenced by increased glucose transporter-4 protein content in skeletal muscle [147].…”
Section: Mechanismsmentioning
confidence: 99%
“…[35][36][37][38][39] In this study, we found excessive abnormal lipid accumulation in the renal tissue of SHR-HF animals compared with that in WKY-HF groups, which was related to increases in the mesangial matrix, TGF-b1 expression, apoptotic glomerular cells and the infiltration of inflammatory cells into kidneys. These findings are consistent with those of previous studies showing that lipid accumulation in kidneys promotes glomerulosclerosis through the low-density lipoprotein-receptor in mesangial cells, through macrophage chemotaxis, increased production of fibrotic cytokines and direct podocyte injury through oxidative stress.…”
Section: Discussionmentioning
confidence: 93%